Swarm intelligence approach in detecting spatially-independent symmetries in cellular automata - Javid, Mohammad Ali Javaheri; Al-Rifaie, Mohammad Majid; Zimmer, Robert (2015 SAI Intelligent Systems Conference (IntelliSys), 2015)
In late 1940's and with the introduction of cellular automata, various types of problems in computer science and other multidisciplinary fields have started utilising this new technique. The generative capabilities of cellular automata have been used for simulating various natural, physical and chemical phenomena. Aside from these applications, the lattice grid of cellular automata has been providing a by-product interface to generate graphical patterns for digital art creation. One notable aspect of cellular automata is symmetry, detecting of which is often a difficult task and computationally expensive. This paper uses a swarm intelligence algorithm - Stochastic Diffusion Search - to extend and generalise previous works and detect partial symmetries in cellular automata generated patterns. The newly proposed technique tailored to address the spatially-independent symmetry problem is also capable of identifying the absolute point of symmetry (where symmetry holds from all perspectives) in a given pattern. Therefore, along with partially symmetric areas, the centre of symmetry is highlighted through the convergence of the agents of the swarm intelligence algorithm. This technique is potentially applicable in the domain of aesthetic evaluation where symmetry is one of the measures.